Penerapan Teknik Forward Chaining dan Certainty Factor Untuk Mendeteksi Penyakit Gastroesophageal Reflux Disease (GERD) - Dewantika, Putri; Lubis, Adi Prijuna; Putri, Pristiyanilicia (Forum Kerjasama Pendidikan Tinggi, 2022)
In this day and age, the lifestyle of people who always want to be practical and always delay eating time causes the body susceptible to disease, this unhealthy habit that makes the stomach produce excess acid that triggers the onset of Gastroesophageal Reflux Disease (GERD). Gerd disease is often considered mild by the public, but if left unchecked then the disease becomes very dangerous because it can irritate the lining of the esophagus and make it become inflamed. Over time, inflammation can damage the lining of the esophagus causing complications such as bleeding, narrowing of the esophagus, and can attack other organs of the body. Early detection of GERD in the stomach needs to be done to prevent the disease. But because of the lack of public knowledge about the symptoms of this disease and the frequent errors in diagnosing GERD, therefore it is necessary to build an expert system to diagnose GERD-based web. Research conducted by Bandar Pasir Mandoge Health Center because GERD disease is a type of disease that is often experienced by the community, and this type of disease is a disease that has the most number of patients in Bandar Pasir Mandoge Health Center with the number of patients as many as 534 in 2021. The purpose of this study is not to replace the role of humans, but to sub substitution human knowledge into the form of a system, so that it can be used by many people (experts and the general public) in dealing with GERD disease. In the preparation of expert systems, a combination of inference rules with a certain knowledge base is provided by one or more experts in a particular field. Several methods can be used, one of which is Forward Chaining which is a reasoning that starts from the facts to get the conclusion of the fact. The results of web-based expert system research using this forward chaining method can act as an expert to detect types of GERD disease and advice for prevention